Longitudinal plasma amyloid beta in Alzheimer's disease clinical trials. Issue 9 (6th October 2014) - Donohue, Michael C.; Moghadam, Setareh H.; Roe, Allyson D.; Sun, Chung‐Kai; Edland, Steven D.; Thomas, Ronald G.; Petersen, Ronald C.; Sano, Mary; Galasko, Douglas; Aisen, Paul S.; Rissman, Robert A.
Abstract : Introduction: Little is known about the utility of plasma amyloid beta (Aβ) in clinical trials of Alzheimer's disease (AD). Methods: We analyzed longitudinal plasma samples from two large multicenter clinical trials: (1) donezepil and vitamin E in mild cognitive impairment (n = 405, 24 months) and (2) simvastatin in mild to moderate AD (n = 225, 18 months). Results: Baseline plasma Aβ was not related to cognitive or clinical progression. We observed a decrease in plasma Aβ40 and 42 among apolipoprotein E epsilon 4 ( APOE ε4) carriers relative to noncarriers in the mild cognitive impairment trial. Patients treated with simvastatin showed a significant increase in Aβ compared with placebo. We found significant storage time effects and considerable plate‐to‐plate variation. Discussion: We found no support for the utility of plasma Aβ as a prognostic factor or correlate of cognitive change. Analysis of stored specimens requires careful standardization and experimental design, but plasma Aβ may prove useful in pharmacodynamic studies of antiamyloid drugs.